Students psychological well-being during the war: an empirical analysis - Kostruba, Natalia; Polischuk, Zoryna (Psychological Prospects Journal, 2022)
Purpose. The study is aimed at empirically study of the peculiarities of students psychological well-being  during the war.Methods. To achieve the goal, the scale of psychological well-being by K. Riff (adapted by T. D. Shevelenkova, P. P. Fesenko), the scale of subjective well-being by H. Perue-Badu (adapted by M. V. Sokolova), a short five-factor questionnaire were used TIPI personality (Ukrainian adaptation of M. Klimanska, I. Galetska).Results. The conducted empirical analysis of the features of the psychological well-being of students during the war made it possible to reveal that the majority of the respondents recorded an average level of well-being, which is manifested in a holistic, realistic view of life, openness to new experiences, immediacy and naturalness of experiences. This testifies to the students' satisfaction with life in general, psychological well-being and optimistic outlook, despite the conditions of military operations in the country. It was also established that from the five-factor model of personality traits, friendliness is the most pronounced in students, which indicates readiness for compassion, meekness, modesty and affection for others and willingness to help. Statistically significant differences were found in the two groups of interviewees in terms of such indicators as positive relationships with others, personal growth, purpose in life, self-acceptance, and a general indicator of psychological well-being.Conclusions. The conducted empirical analysis of the characteristics of psychological well-being during the war demonstrated that the average level of psychological well-being is characteristic of the majority of respondents. A comparison of indicators of the studied phenomenon in female and male students revealed a number of statistically significant differences. Thus, female students have more trusting relationships with others, care about their well-being, constantly work on personal development and increasing their potential, have clear goals and intentions in life, have a positive attitude towards themselves, accept themselves. Whereas it is more difficult for men to build relationships, be open, have no interests in life, do not engage in self-realization, do not see meaning, do not formulate life goals, are dissatisfied with themselves, want to appear to be someone they are not.